2015
DOI: 10.1007/s00436-015-4588-7
|View full text |Cite
|
Sign up to set email alerts
|

Host immune responses to experimental infection of Plasmodium relictum (lineage SGS1) in domestic canaries (Serinus canaria)

Abstract: Understanding the complexity of host immune responses to parasite infection requires controlled experiments that can inform observational field studies. Birds and their malaria parasites provide a useful model for understanding host-parasite relationships, but this model lacks a well-described experimental context for how hosts respond immunologically to infection. Here, ten canaries (Serinus canaria) were infected with the avian malaria parasite Plasmodium relictum (lineage SGS1) in a controlled laboratory se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
22
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 48 publications
1
22
0
Order By: Relevance
“…Acute infections can cause mortality, particularly in species that have been recently introduced to the parasites (Atkinson, Woods, Dusek, Sileo, & Iko, ). During the acute phase, birds can reduce activity levels and food intake, lose body mass and experience severe declines in both haematocrit and haemoglobin (Atkinson et al., ; Ellis et al., ; Krams et al., ; Mukhin, Palinauskas, Platonova, & Kobylkov, ; Palinauskas, Valkiūnas, Bolshakov, & Bensch, ). Observational field studies, which primarily focus on chronic infection, have found positive (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Acute infections can cause mortality, particularly in species that have been recently introduced to the parasites (Atkinson, Woods, Dusek, Sileo, & Iko, ). During the acute phase, birds can reduce activity levels and food intake, lose body mass and experience severe declines in both haematocrit and haemoglobin (Atkinson et al., ; Ellis et al., ; Krams et al., ; Mukhin, Palinauskas, Platonova, & Kobylkov, ; Palinauskas, Valkiūnas, Bolshakov, & Bensch, ). Observational field studies, which primarily focus on chronic infection, have found positive (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Controlled experimental studies with P. relictum are relatively easy to design due to availability of laboratory-friendly experimental vertebrate hosts (canaries and some species of other common birds), laboratory-colonized susceptible mosquitoes (species of the Culex pipiens complex) and worldwide high prevalence in many wild bird species (donors of natural infections). This makes P. relictum a convenient and even unique model organism to approach numerous questions about mechanisms of host-parasite interactions, including the immunological aspects during malaria infections [ 56 58 ], the ecology and evolution of host-parasite associations [ 25 , 59 63 ], the host adaptations to tolerate malaria infections [ 10 , 31 , 47 , 64 , 65 ], patterns of mosquito transmission [ 32 , 46 , 53 , 66 68 ] and many other questions.…”
Section: Discussionmentioning
confidence: 99%
“…8 Indeed, parasites with similar infection dynamics in Culex vectors (CHI02PL, CHI04PL, and CHI07PL) were apparently specialized American robins 43,44 and had MIRs that generally peaked in late July or early August. In addition, juvenile robins accumulated infections of these parasites contemporaneously, with the most rapid increase in infections occurring in July and August (weeks [25][26][27][28][29][30][31][32][33][34][35].…”
Section: Discussionmentioning
confidence: 99%
“…26 If the host survives the acute infection, parasitemia in the blood often declines to lower levels. Low parasitemia in the blood generally persists through this chronic stage of infection, 27 and parasites may disappear from the blood stream, lying dormant in tissues. Relapses and recrudescence of low-level or dormant malaria infection may occur, especially during periods of host stress.…”
Section: Introductionmentioning
confidence: 99%